Perlindungan Hukum Calon Pekerja dalam Pelaksanaan Pelatihan Vokasi di PT X - Enge Christina; Agustin Widjiastuti; Andyna Susiawati (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2024)
Vocational training in Indonesia is organised based on cooperation or mutual agreement between educational institutions and companies. This research highlights the unavailability of legal regulations that specifically protect vocational trainees. The lack of specific regulations causes the implementation of existing labour regulations to be limited to companies where vocational training is held. Through this normative jurisprudence research, it can be seen that the vacuum legis condition, namely the existence of a vacuum of specific legal rules, has begun to have a solution. The Indonesian government has actually started to improve the quality of human resources through vocational education and training by making three new regulations related to vocational training. There are three new regulations that have been issued, namely: Presidential Regulation No. 68 of 2033 concerning Revitalisation of Vocational Education and Vocational Training issued on 27 April 2022. Coordinating Minister for Human Development and Culture Regulation No. 5 of 2022 governing the Organisation and Working Procedures of the National Coordination Team for Revitalising Vocational Education and Vocational Training, promulgated on 14 September 2022. Coordinating Minister for Human Development and Culture Regulation No. 6 of 2022 on the National Strategy for Vocational Education and Vocational Training, also promulgated on 14 September 2022. It is expected that these regulations can be implemented to protect the individual rights of prospective workers in vocational training in Indonesia.